The Characteristics of Natural Killer Cells in Chronic Hepatitis B Patients Who Received PEGylated-Interferon versus Entecavir Therapy. (27th January 2021) - Cao, Weihua; Li, Minghui; Zhang, Lu; Lu, Yao; Wu, Shuling; Shen, Ge; Chang, Min; Liu, Ruyu; Gao, Yuanjiao; Hao, Hongxiao; Hu, Leiping; Yi, Wei; et al.
Abstract : Background . To explore the role of natural killer (NK) cells in the process of hepatitis B virus (HBV) clearance and whether their phenotype is related to antiviral treatment outcome in chronic hepatitis B (CHB) patients. Method . We performed a single-center prospective cohort study to analyze changes of NK cells at weeks 12 and 24 from baseline in CHB patients who received PEGylated-interferon- (PEG-IFN-) α -2a versus entecavir. The frequencies of NK, CD56 bright, CD56 dim, IFNAR2 +, NKp46 +, NKp46 bright, and NKp46 dim NK cells and mean fluorescence intensity (MFI) of receptors NKp46 and IFNAR2 on the surface of NK cells were measured. Subgroup analyses were performed by comparing treatment responders versus nonresponders with aforementioned parameters in each group. Results . In PEG-IFN- α -treated patients, posttreatment CD56 bright NK cell frequency increased, but CD56 dim NK cell frequency decreased. Additionally, receptor NKp46 and IFNAR2 expression enhanced. In entecavir-treated patients, although NK cell frequency increased, CD56 bright and CD56 dim NK cell frequencies and IFNAR2 expression did not differ between baseline and posttreatment. In subgroup analyses, posttreatment CD56 bright NK cell frequency and IFNAR2 expression significantly increased in PEG-IFN- α responders from baseline, while changes were absent in PEG-IFN- α nonresponders and entecavir treatment responders. Among patients with HBV viremia after entecavir therapy, NK cell frequency significantly increased, whereas NKp46 bright and IFNAR2 + NK frequency and IFNAR2 MFI significantly decreased at 12 and 24 weeks from baseline. Conclusions . In CHB patients, PEG-IFN- α treatment significantly enhanced NK cell frequency and function when compared to entacavir. Positive treatment responses to either interferon or entecavir were associated with NK cell function improvement. This trial is registered with clinical trial registration no. NCT03208998 .